The Implementation of Economic Systems in International Trade and Free Trade in Indonesia from a Justice Perspective - Eddie Bachtiar Siagian; Cendy Wenas; Diana R. W. Napitupulu (Inovasi Pratama Internasional. Ltd, 2025)
This paper discusses the application of the economic system in the Republic of Indonesia within the context of international trade and free trade from the perspective of legal justice, which is, of course, based on Pancasila and the 1945 Constitution (UUD 1945). Considering the abundance of legislative products up to their organic regulations, there has been, normatively, no visible equitable distribution of outcomes, especially in the provinces, cities, and regencies in Indonesia that serve as sources of natural resources. Therefore, this paper becomes significant to present. International trade and free trade, which have been widely recognized for many years, carry a rather proud and somewhat exclusive impression. However, when compared to the implementation of the existing and prevailing laws and regulations, they still appear to be mere spectacles. This study employs a normative juridical method, which emphasizes the analysis of various laws and regulations, as well as academic writings such as theses, dissertations, and journals related to the topic.